Acacia gum: History of the future. (May 2018) - Sanchez, C.; Nigen, M.; Mejia Tamayo, V.; Doco, T.; Williams, P.; Amine, C.; Renard, D.
Abstract: On behalf of the 90 th birthday of Professor Glyn O. Phillips, it is a great honor for authors of this publication to make a review on Acacia gum, one of the favorite polysaccharides extensively studied by Glyn and his collaborators all around the world during these last five decades. After remembering a synthetic historical perspective, the present critical review summarizes the main updated data of this complex polysaccharide from the chemical composition to the functional properties with a particular attention toward structure and bulk and interfacial properties. Biological properties of Acacia gums were not considered. Some of the main challenges in a near future for a better understanding of the functional properties of this polysaccharide concerns the detailed study of the gum maturation mechanism upon exudation, the structure and conformation of different molecular fractions, the role of minor components (minerals, polyphenols, lipids) on the structure and functionality of gums, the physicochemical properties of purified molecular fractions and the ways to modified them upon enzymatic modifications. In our opinion, the main challenges for a better understanding of the interfacial function of this polysaccharide (adhesion and stabilization at liquid and solid interfaces) will be to probe the interfacial induced conformational changes. This area of research seems to have been quite neglected during these last past years and fundamental questions arising from the adhesive and stabilizing properties of Acacia gum are still without answer today. In addition, the amino-acid sequence contained in this complex polysaccharide are totally unknown today and future developments based on enzyme/chemical modifications and liquid chromatography coupled to on line mass spectrometry could unravel the sequence and decipher between the existence of one or more amino-acid sequences in Acacia senegal gum. We sincerely hope Glyn, one of the "father of Arabic gum", will find some positive echo in this review. Graphical abstract: Image Highlights: Acacia Senegal gums are made of three molecular fractions and minor components. Molecular fractions structures are extensively reviewed. Hydration, rheological and interfacial properties of Acacia gum are discussed. Interfacial properties of Acacia gums are related to high Mw components content. Future research areas are identified including major challenges and bottlenecks.